Valuation of Information Technology Investment Using the Discounted Cash Flow and Real Options Analysis - Triastiti, Lely; Anggono, Achmad Herlanto (Jurnal Manajemen Teknologi, 2012)
PT. Telekomunikasi Indonesia (Telkom) planned to develop an IT-based integrated Customer Relationship Management (CRM) system called Unified TICARES in 2012 as a part of corporate strategic initiatives. The key question is whether the value of this investment is truly feasible for the company. The purpose of this thesis is to provide an IT-based investment valuation analysis using two approaches, namely the discounted cash flow (DCF) and real options analysis (ROA). It compares the results to find out whether different approach will arrive to different conclusions about the investment feasibility. The finding result from both approaches show that Unified TICARES is a promising investment, indicated by positive NPV. However, the result with ROA did not show much difference against the DCF approach. It indicates that the use of ROA is not always necessary to value an investment due to its complexity. The usefulness of ROA will be visible in valuing investments that involve complex configurations. ROA is also required when DCF is not sufficient to provide quantitative judgment on project that subject to high risk and uncertainty.